2002
DOI: 10.1007/s100670200127
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipoprotein(a) Level and its Clinical Significance in Patients with Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a classic autoimmune disease characterised by the production of autoreactive T cells and autoantibodies that may affect every organ system. It has long been established that there is a close association between cholesterol- rich lipoproteins (such as low-density lipoprotein-cholesterol) and cardiovascular disease in patients with SLE. In this study, we evaluated total cholesterol, triglycerides, HDL-cholesterol, LDL-cholesterol, VLD-cholesterol, apolipoprotein A-1, apolipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 21 publications
2
23
1
1
Order By: Relevance
“…Cross-sectional studies of patients with differing degrees of disease activity and steroid dosages have generally demonstrated elevated mean triglyceride levels, while total cholesterol levels have been either normal or elevated. Similar variability in low-density lipoprotein (LDL) cholesterol and HDL cholesterol levels have been seen (13,16,23,24,27,(31)(32)(33). None of the studies published thus far have reported longitudinal data on lipid levels at fixed time points or evaluated large numbers of pediatric patients at presentation and at times of differing disease activity in order to better differentiate the effects of disease activity and steroid treatment.…”
mentioning
confidence: 76%
“…Cross-sectional studies of patients with differing degrees of disease activity and steroid dosages have generally demonstrated elevated mean triglyceride levels, while total cholesterol levels have been either normal or elevated. Similar variability in low-density lipoprotein (LDL) cholesterol and HDL cholesterol levels have been seen (13,16,23,24,27,(31)(32)(33). None of the studies published thus far have reported longitudinal data on lipid levels at fixed time points or evaluated large numbers of pediatric patients at presentation and at times of differing disease activity in order to better differentiate the effects of disease activity and steroid treatment.…”
mentioning
confidence: 76%
“…Dyslipidemia with decreased highdensity lipoprotein (HDL) and elevated triglycerides, LDL, and lipoprotein(a) has been associated with cumulative SLE disease activity and disease damage [35,36]. Lipoprotein(a), a cholesterol-rich lipoprotein, has been identifi ed as an independent risk factor for CVD [37].…”
Section: Dyslipidemia Increased Oxidative Stress and Impaired Antiomentioning
confidence: 99%
“…Lipoprotein(a), a cholesterol-rich lipoprotein, has been identifi ed as an independent risk factor for CVD [37]. It has been shown to be signifi cantly elevated in SLE patients compared with healthy controls (P < 0.01) [36]. Lipoprotein(a) has also been found to be associated with coronary artery calcifi cation in SLE patients [14,36,38].…”
Section: Dyslipidemia Increased Oxidative Stress and Impaired Antiomentioning
confidence: 99%
See 1 more Smart Citation
“…Adults and children with cardiovascular disease without underlying inflammatory disease like SLE also have elevated cytokines and autoantibodies to oxidized LDL components. Most cardiovascular risk factors are common to both groups, such as elevated Lp(a) [40], homocysteine, lupus anticoagulant [4], the traditional Framingham risk factors, and others.…”
Section: Causes Of Dyslipoproteinemia In Systemic Lupus Erythematosusmentioning
confidence: 99%